Between “ghettos”, “safe spaces” and “gaytrification” - Costa, Pedro (2019)
In recent decades, “LGBT neighbourhoods” or “gay Villages” have been gaining some prominence and particular identity characteristics within cities. As other areas that have been the main drivers of urban revitalization of inner cities, such as cultural and creative quarters or multicultural spaces, these territories stand out for their users and residents’ social practices, the specificities of their economic activity, or their contribution to creativity or social integration. More than community ghettos, these areas have been characterized by their openness and vibrancy, enhancing the coexistence of diverse lifestyles, trajectories and identities, but also by the contribution of LGBT people to the spatial gentrification through their strong commercial, residential and symbolic presence. Drawing upon an empirical work developed in Lisbon (Príncipe Real district) and Madrid (Chueca district), based on in-depth interviews to LGBT residents and participant observation in these two neighbourhoods, this paper characterizes the main evolutionary trajectories and specificities of these two quarters. An analysis is made confronting the characteristics and contingencies of these areas with other previously studied cases in literature, identifying the existence of notable differences and suggesting evidence of significant specificities, which can constitute a “South European” approach to the reality of “gay Villages”. Some generic principles for urban planning are drawn out from the analysis.